Kids and Kilowatts: Socialisation, energy efficiency, and electricity consumption in New Zealand. (October 2018) - Aguirre-Bielschowsky, Ikerne; Lawson, Rob; Stephenson, Janet; Todd, Sarah
Highlights: Socialisation into energy saving practices is intense in 9–10-year-old children. NZ children use a wide range of electrical appliances at home. Modelling, reminders and rules are key energy saving socialisation processes. Lack of control over appliances hinders children's ability to learn to save energy. Children are often not energy conscious when engaging in energy saving practices. Abstract: Socialisation into electricity consumption usually occurs during childhood, but little is known about the socialisation processes involved. Here, we use interviews and focus groups to investigate how nine to ten-year-old children from New Zealand learn about, and consume, electricity in their homes. The children used a wide range of electrical appliances and engaged in different energy saving behaviours, often without being conscious of their implications. Control over appliances and learning through modelling, reminders and rules helped to socialise children into saving electricity, while nagging and inconsistent behaviours from parents were counterproductive. Conversations about energy were uncommon, but helpful for creating consciousness about energy use. We discuss the need for a more structured approach, through developing energy literacy, in order for children to use their agency, surpass their parents' level of energy saving practices, and stabilise energy saving behaviours through life. In addition, we provide recommendations on how parents, schools, the media and product developers can help in this process.